2014
DOI: 10.1097/iae.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Structure After Closed-Globe Blunt Ocular Trauma

Abstract: Purpose To evaluate outer retinal structural abnormalities in patients with visual deficits following closed globe blunt ocular trauma (cgBOT). Methods Nine subjects with visual complaints following cgBOT were examined between 1 month post-trauma and 6 years post-trauma. Spectral domain optical coherence tomography (SD-OCT) was used to assess outer retinal architecture, while adaptive optics scanning light ophthalmoscopy (AOSLO) was used to analyze photoreceptor mosaic integrity. Results Visual deficits ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 47 publications
2
36
1
Order By: Relevance
“…The split-detector AOSLO images revealed a mosaic of enlarged photoreceptors in the area of EZ and IZ disruption, surrounded by apparently normal cone and rod photoreceptors. Notably, the disruption size on confocal AOSLO more closely mirrors the size of the IZ disruption as previously reported 20 (Figure 5); whereas split-detector AOSLO demonstrates there is not complete loss of the photoreceptor mosaic as the EZ disruption might suggest. The dark vertical stripes in the confocal image are likely vessel shadows, which appear as a blur in the split-detector image.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The split-detector AOSLO images revealed a mosaic of enlarged photoreceptors in the area of EZ and IZ disruption, surrounded by apparently normal cone and rod photoreceptors. Notably, the disruption size on confocal AOSLO more closely mirrors the size of the IZ disruption as previously reported 20 (Figure 5); whereas split-detector AOSLO demonstrates there is not complete loss of the photoreceptor mosaic as the EZ disruption might suggest. The dark vertical stripes in the confocal image are likely vessel shadows, which appear as a blur in the split-detector image.…”
Section: Resultssupporting
confidence: 83%
“…20 Briefly, subject WW_0923 (22-year-old male) was an unrestrained driver in a motor vehicle collision in which airbags were deployed. Clinical evaluation on post-trauma day 2 revealed commotio retinae and RPE changes within the macula, as well as wide-spread hemorrhaging in the posterior pole OU.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the combination of fundus examination, SD-OCT, and AO-SLO may be useful in accurately diagnosing macular microholes and for monitoring patients with the disease. Recently Flatter et al 40 reported the SD-OCT and AO-SLO findings of photoreceptor damage after blunt trauma, which are similar to those of macular microholes. In both conditions, the lesions were very small, and AO-SLO is useful for evaluating and monitoring patients.…”
Section: Discussionmentioning
confidence: 59%